Time-differentiated distribution of service parts and repair materials: an investigation of service time, area partitions, and cost relations - Jat, Mohsin Nasir (2015)
Motivation: Manufacturers in sectors like Information Technology (IT), Automotive and Aerospace have increasingly become focused on providing after sales services. One of the forms of after sales services is to provide service parts (or spare parts) to customers within different contracted time windows. Commonly offered by large scale IT sector companies, such services are facilitated by Service Parts Logistics (SPL) systems through a network of parts stocking facilities. The number of stocking facilities in a distribution network affects the service responsiveness and service costs related to inventory, transportation and facility set-up. Higher responsiveness can be attained through increasing the number of facilities in a distribution network, which, in turn, usually increases inventory cost. Generally, studies assume that shorter service time windows result in higher costs, but there is a lack of exploration regarding how reductions in service time limits and changes in the fractions of demand for different time-based service types impact on various service related costs. Service area partitioning (or zoning) is another related issue which is unexplored in general facility location literature when considering multiple service time (or distance) constraints and both inventory and transportation costs.